2004
DOI: 10.1093/abbs/36.10.701
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bovine IFN-α on the Immune Response in Guinea Pigs Vaccinated with DNA Vaccine of Foot-and-Mouth Disease Virus

Abstract: In this study, we constructed recombinant plasmid pcDNA3.1/P12X3C3D including P1, 2A, 3C, 3D and part of 2B gene of FMDV and pcDNA3.1/IFN containing the gene encoding bovine IFN-alpha. We inoculated the DNA vaccine pcDNA3.1/P12X3C3D with or without pcDNA3.1/IFN to evaluate the efficiency of this DNA vaccine and the immunogenicity of DNA vaccine enhanced by the co-delivery with pcDNA3.1/IFN. After two times of vaccination with DNA vaccine, all of guinea pigs were challenged with 103 ID50 FMDV type O. Anti-FMDV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The antibody titers in immunized guinea pigs were determined by indirect-ELISA as described elsewhere [36,37]. Briefly, 96-well plates were coated with inactivated FMDV Asia1/Jiangsu/China/2005 (100 mL/well) in 0.05 M bicarbonate buffer (pH 9.6) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The antibody titers in immunized guinea pigs were determined by indirect-ELISA as described elsewhere [36,37]. Briefly, 96-well plates were coated with inactivated FMDV Asia1/Jiangsu/China/2005 (100 mL/well) in 0.05 M bicarbonate buffer (pH 9.6) at 4°C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Guo used bovine IFN-a and DNA Vaccine of Foot-andMouth Disease Virus to vaccinate Guinea pigs. The result indicated that IFN-a could enhance the effect of T-lymphocytes proliferation (Guo et al, 2004). In our study, we used pcDNA-SDIFN-a to inoculate 28-day-old ducks at different doses by gene gun.…”
Section: Effect Of T-lymphocytes Proliferationmentioning
confidence: 90%
“…After cloning the HN region in the eukaryotic expression vector pcDNA3.1, which is commonly used for high-level stable expression in mammalian cells [27-30], its expression was analyzed in Vero-transfected cells. We found that the pcDNAHN176-construct over expressed the corresponding RNA and polypeptide.…”
Section: Discussionmentioning
confidence: 99%